Outbreak of diarrhea among preweaning alpacas (Vicugna pacos) in the southern Peruvian highland - Rojas, Miguel; Manchego, Alberto; Rocha, Camila B; Fornells, Luz Alba; Silva, Raquel C; Mendes, Gabriella S; Dias, Helver G; Sandoval, Nieves; Pezo, Danilo; Santos, Norma (The Journal of Infection in Developing Countries, 2016)
Introduction: Infections, particularly diarrheal infections, are a major cause of neonatal death in South American camelids. The aim of this study was to identify the pathogens that could have caused the recent diarrhea outbreak among the alpacas in Silli, Cusco, located in the southern Peruvian highland. Methodology: Spleen, kidney, and intestine tissue along with fecal and intestinal lavage samples were obtained from 50 one- to five-week-old alpacas and analyzed for the presence of parasites, bacteria, and viruses. Results: Laboratory testing of the 50 crias included in this study revealed that 80% were infected with Eimeria spp., 40% with coronavirus, 34% with E. coli, 32% with rotavirus, 22% with Clostridium spp., and 20% with Cryptosporidium spp. Of these 50 alpaca crias, 20 presented with a single infection (19 positive for Eimeria spp. and 1 positive for rotavirus). Co-infections with up to four pathogens occurred in 60% of the samples. The significance of such infections is not clear, but it is noteworthy that the animals suffering from necrotic and/or hemorrhagic enteritis presented with quadruple infections. It is likely that co-infections increase the severity of the disease. Conclusions: These data show that multiple pathogens circulate among young alpaca crias and could be associated with diarrheal disease in these animals. The findings from this study warrant the provision of subsidies for future assessment of the potential economic impact of these infections on the productivity of the Peruvian alpaca industry.